Improving Reading Comprehension Through Collaborative Strategic Reading - Jimmi Daniel (LPPM Universitas Bina Sarana Informatika, 2016)
The objective of this paper is to know how to teach collaborative strategic reading and teaching reading by using CSR. This paper uses descriptive qualitative method by searching any references to accomplish this analysis. The data were collected through observation, teaching learning process and evaluation. This program contains the planning, how to implement the students’ reading comprehension through Collaborative Strategic Reading (CSR). The post-test was a mean to evaluate the action conducted in this field study. The teacher uses collaborative strategic reading to get the goal of teaching. In general, the results of this field study show that teaching English reading comprehension through collaborative strategic reading has advantages, disadvantages, and impacts: (1) The advantages are improving students’ ability in reading comprehension and increasing students’ English learning motivation, (2) The disadvantages are some group`s members lack contribute to the activity and seriousness is lacking, (3) The impacts are students are working and learning together and also collaborative strategic reading allows students to be more engaged and involved in the learning process, instead of being just passive learners.Keywords: Teaching, Reading, Collaborative Strategic Reading